Evaluasi Daya Pemulih Kesuburan Padi Lokal dari Kelompok Tropical Japonica - Hairmansis, Aris; Aswidinnoor, Hajrial; Trikoesoemaningtyas, ,; Suwarno, , (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
Twenty seven land races of tropical japonica rice were test-crossed with a 'WA' type cytoplasmic male sterility (CMS) line IR58025A to evaluate their fertility restoration ability. Based on pollen fertility and spikelet fertility of their F1 hybrids, genotypes are classified into maintainer or restorer. The result showed frequency of maintainers among genotypes was higher than restorers. Four genotypes, i.e., Ase Lapan, Ase Mandi, Hawara Bunar and Lampung Kuning were designated as maintainers. These maintainers possess a number of desirable traits such as pest resistance and abiotic stresses tolerance; thus they will be useful for improving parental lines of hybrid rice. Key words: Land race, test cross, fertility restoration